Fun Science: Roket Air Sebagai Media Edu-Sains untuk Meningkatkan Motivasi Belajar Peserta Didik Sekolah Dasar - Pina Pitriana; Rena Denya Agustina; Rizki Zakwandi; Muhammad Ijharudin; Dede Trie Kurniawan (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2018)
Learning science is considered to be difficult and complicated for most students since it requires high reasoning and imagination. This study aims to increase the motivation of students in Primary School to learn science using water rockets interspersed with game. The results of the research show that there is an increase in learning motivation of learners in Lesson Subject. The design of training and games connected with PAKEM shows a positive and intensive response for students. The results showed that more than 90% of the learners provide a positive response to learning. In addition, students’ motivation and learning activities were improved during the learning process.